Time and day: trends in student access to online asynchronous courses in communication demonstrate time poverty in action - LeBlanc, H. Paul (Frontiers in Education, 2023)
Objective As changes to higher education following the rapid transition to online learning resulting from the COVID-19 pandemic impacted students and their perceptions of what is possible in scheduling their daily lives around school, this study investigates trends in student access to online asynchronous courses. Methods This study utilized course reports of student access from the learning management system for thirty-one sections of eleven different online asynchronous communication courses taught by ten different faculty members over the fall and spring semesters at a large research university in the southwestern United States. A total sample size of 1,201 students were involved in the study. Results Profile Analyses indicate clear curvilinear trends for time of day and day of the week in student course access. Repeated Measures ANOVA results indicate those trends vary significantly from a no effect condition, suggesting that students: (a) schedule their course activities around personal schedules, and (b) that time bound synchronous course may not work for them. Conclusion Recommendations for class management by instructors relating to student time poverty need regardless of teaching modality, and future directions for research on time poverty in higher education, are provided.